The Analysis of Activity-Based Management Implementation to Increase Cost Efficiency in Hotel XY Semarang - Nadzifah Sabila Husna; Mohamad Hasanudin; Musyafa Al Farizi Farizi (Yayasan Ilomata, 2022)
Hotel XY Semarang is a star hotel that provides various services and facilities, so it is necessary to increase cost efficiency without reducing the value provided to customers. This study aims to analyze the cost efficiency of activities by applying the Activity-Based Management method using accurate cost information to reduce non-value-added activities. This study uses a quantitative descriptive method. The data were collected through observation, interviews, and documentation. This study first calculated the room rental cost using Activity-Based Costing, then calculated the value of cost efficiency with the Activity-Based Management method and tested the hypothesis to determine whether there is a significant difference after the implementation of Activity Based Management. The results showed that Hotel XY Semarang still calculates room rental costs using the traditional method. After implementing the Activity Based Costing method, the results show the difference in under costing in the President Suite room types and over costing in the Deluxe Room, Junior Suite, and Executive Suite room types. The implementation of Activity Based Management can reduce costs by Rp. 734.526.570 or increase cost efficiency by 7.91% of the total cost of Rp. 9.287.146.443.